1988
DOI: 10.1111/j.1476-5381.1988.tb16552.x
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic antidepressants block N‐methyl‐D‐aspartate receptors: similarities to the action of zinc

Abstract: 4 Desmethylimipramine, imipramine and ketamine also prevented the Ca2+ influx into cultured cortical neurones of the rat produced by N-methyl-D-aspartate. 5 As the actions of tricyclic antidepressants in this system are not competitive with respect to N-methyl-D-aspartate, glycine or MK-801, and as they slow the dissociation of [3H]-MK801, we conclude that tricyclic antidepressants may be acting at the Zn2 + recognition site on the N-methyl-D-aspartate receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(83 citation statements)
references
References 29 publications
3
76
2
2
Order By: Relevance
“…In particular, the work of Ö gren and Goldstein 36 has shown that three dopamine antagonists (haloperidol, raclopride and remoxipride) blocked locomotion elicited by low and high doses of phencyclidine. Because these three dopamine antagonists have very low affinity for the NMDA receptor, 37 with raclopride and remoxipride being highly selective for dopamine D2 receptors, 38,39 dopamine must be an important component in the phencyclidine hypoglutamate model of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the work of Ö gren and Goldstein 36 has shown that three dopamine antagonists (haloperidol, raclopride and remoxipride) blocked locomotion elicited by low and high doses of phencyclidine. Because these three dopamine antagonists have very low affinity for the NMDA receptor, 37 with raclopride and remoxipride being highly selective for dopamine D2 receptors, 38,39 dopamine must be an important component in the phencyclidine hypoglutamate model of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…39 In this study, the NMDA antagonist, ketamine, did not modify sensitivity to glycine, although it directly reduced NMDA receptor function through blockade of the calcium channel within the NMDA receptor complex. The tricyclic antidepressant, desipramine, which has direct NMDA receptor antagonism at therapeutic doses, 40,41 reduces the potency of glycine to displace 5,7-DCKA binding similarly to other antidepressants, and it also reduces the density of 5,7-DCKA binding sites. 39 In humans, the antidepressant activity of NMDA receptor antagonists received little rigorous evaluation.…”
Section: Glutamatergic Abnormalities In Mood Disordersmentioning
confidence: 99%
“…Moreover, the antihistaminergic action of TCAs may have a general analgesic effect (Rumore and Schlichting, 1986). Recent findings have shown that antidepressants also interact with the opioidergic system (Gray et al, 1998) and that they act as NMDA-receptor antagonists (Reynolds and Miller, 1988). Antidepressants, especially selective serotonin reuptake inhibitors (SSRIs) and TCAs, are also indicated for anxiety disorders, including generalized anxiety disorder, panic disorder, obsessive-compulsive disorder, and posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%